Potassium channel TASK-5 forms functional heterodimers with TASK-1 and TASK-3 to break its silence - Susanne Rinné; Florian Schick; Kirsty Vowinkel; Sven Schütte; Cornelius Krasel; Silke Kauferstein; Martin K.-H. Schäfer; Aytug K. Kiper; Thomas Müller; Niels Decher (Nature Communications, 2024)
Abstract TASK-5 (KCNK15) belongs to the acid-sensitive subfamily of two-pore domain potassium (K2P) channels, which includes TASK-1 and TASK-3. TASK-5 stands out as K2P channel for which there is no functional data available, since it was reported in 2001 as non-functional and thus “silent”. Here we show that TASK-5 channels are indeed non-functional as homodimers, but are involved in the formation of functional channel complexes with TASK-1 and TASK-3. TASK-5 negatively modulates the surface expression of TASK channels, while the heteromeric TASK-5-containing channel complexes located at the plasma membrane are characterized by changes in single-channel conductance, Gq-coupled receptor-mediated channel inhibition, and sensitivity to TASK modulators. The unique pharmacology of TASK-1/TASK-5 heterodimers, affected by a common polymorphism in KCNK15, needs to be carefully considered in the future development of drugs targeting TASK channels. Our observations provide an access to study TASK-5 at the functional level, particularly in malignant cancers associated with KCNK15.